Exploring Teaching Practices in Arabic Language Education: A Qualitative Case Study at an Indonesian Islamic Boarding School - Muzakki Abdurrahman; Linura Tuada; Nurul Ilma; Sovia Fahraini; Hisbullah Huda (Abjadia : International Journal of Education, 2026)
Learning Arabic language is essential in Islamic and formal education, especially in institutions that aim to equip learners with linguistic ability and good character. Bilingual schools involve various factors in the teaching and learning process such as institutional policy, learners' background, and teaching approach. This study aims to examine the practice of Arabic language teaching and learning in SMP Bilingual Terpadu Krian Sidoarjo using a qualitative method. Classroom observations were conducted in 12 meetings over two months, followed by semi-structured interviews with one Arabic language teacher and five selected eighth grade students, as well as document analysis. The results indicate that Arabic language teaching practices apply a mixed instructional strategy combining direct explanation and interactive activities, which support both conceptual understanding and active student involvement. Student participation tends to be dynamic, influenced by lesson design, language proficiency, and self-confidence. The use of bilingual instruction helps students understand the material more easily; however, it may reduce exposure to the target language. Challenges include varying levels of student ability and inconsistent participation, while supporting factors include flexible teaching strategies, diverse techniques, and a positive classroom atmosphere. This study provides insights into Arabic language teaching practices in bilingual schools and highlights important considerations for improving effective teaching and learning processes.